Current Ratio, Debt to Equity Ratio, dan Return on Asset terhadap Return Saham - Hasanudin Hasanudin (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, and Return On Assets on Stock Returns in telecommunication services sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. This research method is descriptive quantitative. This data source uses secondary data in the form of financial statements from each of the telecommunications services sub-sector companies from 2017-2021. The method used in this study is multiple linear regression using the EVIEWS 9 application. The results show, Current Ratio (CR) has a positive and insignificant effect on stock returns, Debt to Equity Ratio (DER) has a negative and insignificant effect on stock returns, and Return on Assets (ROA) has a negative and insignificant effect on Stock Return. Conclusions, a) the size of the Current Ratio does not necessarily produce a high return, b) the company experiences a decrease in the value of the company if there is an increase in debt in the company; c) changes in the value of return on assets will give a negative contribution to stock returns. However, if ROA increases, the company will get a low share return contribution or vice versa, a smaller change in the value of return on assets will have an impact on higher stock returns. Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets, Stock Return